Language change and language structure : older Germanic languages in a comparative perspective - Swan, Toril; Mørck, Endre, 1952-; Westvik, Olaf Jansen, 1943- (Trends in linguistics. Studies and monographs, 1994)
Language Change and Language Structure : Older Germanic Languages in a Comparative Perspective Trends in Linguistics. Studies and Monographs [TiLSM].